Extraordinary Leadership Abilities in Empowering Women’s Political Representation in Malaysia - Nor Rafidah, Saidon; Mohd Hisyamuddin, Basabah; Mohd Nabil, Mohd Nor Azan; Zolhizir, Daud; Nurul Asmaa, Ramli; Ain Nadirah, Romainor (Forester Communications Inc., 2026)
Women’s participation in national legislative bodies, local governments, and peace-building processes can potentially change the current political landscape, including the future. The presence of women in politics will alter societal views towards women and girls and their roles in decision-making. This research paper discusses women’s extraordinary abilities in empowering women’s political involvement in Malaysiafrom 1980 to 2013. This study also aims to examine the exceptional characteristics of women who reached the highest level at either party or national level leadership. The research method used for this study is qualitative, which includes a combination of observation and interviews with a selected number of respondents among former cabinet ministers or current members of the cabinet, scholars studying genders, and Members of Parliament as well as the State Assemblymen. In addition, the researcher also obtained secondary data related to the study. Following that, the data and tables obtained from credible sources were subsequently analysed using qualitative methods. The conceptual frameworks adopted for this study include the theory of leadership, the concept of empowerment and the concept of gender. The findings from the study reveal that although women’s political awareness is increasing, the opportunity for them to compete at the highest level remains a challenge due to the lack of readiness among party leadership to place and hope for women candidates as their primary choice, particularly in parties such as UMNO, PAS, MIC, and others